Cites and facts in the news: polyphony in press discourse - Amado, Adriana (Romanica Olomucensia, 2014)
This article presents some enunciation theory ideas integrated with journalism studies to propose an enhanced model for discourse analysis of news. It recommends distinguishing the subjects of the enunciation from the subjects of the statements (enonce) in order to identify journalists and sources' voices in the news discourse. This approach considers journalistic objectivity as a newsmaking ritual that gives clues of the process by which a statement become news. Considering the polyphony inherent to news, this concept applied to discourse analysis could explain how newspapers with different orientation, ideologically and commercially speaking, offer the same coverage.
Keywords: polyphony; enunciation; news discourse.